Managing Social Media Ethics in Islamic Boarding Schools: Challenges and Strategies for Crisis Response - Ahmad Nadif Sanafiri; Muhyidin; Rizkiyah Hasanah (Managere: Indonesian Journal of Educational Management, 2024)
This study aims to explore the management of ethical issues in dealing with social media crises by Islamic boarding schools, focusing on the strategies implemented to maintain the institution's image and public trust. The research approach used is qualitative with a case study design. It takes Nurul Jadid Islamic Boarding School as the research subject because of its active social media activities and experience in handling various digital crises. Data were collected through semi-structured interviews with social media managers and Islamic boarding school leaders, observations of Islamic boarding school social media activities, and analysis of digital documents in the form of uploads, comments, and responses to emerging issues. Data analysis techniques were carried out thematically by identifying relevant patterns from the collected data and triangulation to ensure the validity of the findings. The results of the study indicate that Islamic boarding schools face a dilemma in balancing social media trends with religious values, challenges in responding to diverse audiences ethically, and the lack of a structured crisis management strategy. These findings emphasize the importance of value-based social media crisis management to maintain the integrity of religious institutions in a dynamic digital era.